2011
DOI: 10.1242/jeb.047316
|View full text |Cite
|
Sign up to set email alerts
|

Ordinary glomeruli in the antennal lobe of male and female tortricid moth Grapholita molesta (Busck) (Lepidoptera: Tortricidae) process sex pheromone and host-plant volatiles

Abstract: Couto et al., 2005). In moths, plant odour processing occurs mainly in the ordinary glomeruli (Christensen and Hildebrand, 2002; Christensen and White, 2000) and pheromone processing occurs in distinct glomeruli, the macroglomerular complex (MGC) (Anton and Homberg, 1999;Hansson et al., 1992 Accepted 18 October 2010 SUMMARY Both sexes of Grapholita molesta, a key pest of stone fruits, are able to detect host-plant volatiles and the sex pheromone emitted by females, and to modify their behaviour accordingly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 72 publications
2
17
0
Order By: Relevance
“…Excitatory responses of MGC PNs to plant odours have also been reported for S. littoralis (Anton and Hansson, 1995), and inhibitory responses of MGC PNs to plant odours were described in M. sexta (Reisenman et al, 2008). Similar evidence has been found in the tortricid moths Cydia pomonella and Cydia molesta, where responses to plant odours were found in MGC neurons and pheromone responses in PNs within other glomeruli (Trona et al, 2010;Varela et al, 2011b). Such results are in agreement with data from vertebrates, where both 'common' odours and pheromones can activate the main olfactory bulb and the accessory olfactory bulb (Xu et al, 2005), and thus overlapping processing of both odour types occurs in both compartments of the primary olfactory centre.…”
Section: Mgc Neurons Are Sensitive To a Behaviourally Relevant Plant supporting
confidence: 63%
“…Excitatory responses of MGC PNs to plant odours have also been reported for S. littoralis (Anton and Hansson, 1995), and inhibitory responses of MGC PNs to plant odours were described in M. sexta (Reisenman et al, 2008). Similar evidence has been found in the tortricid moths Cydia pomonella and Cydia molesta, where responses to plant odours were found in MGC neurons and pheromone responses in PNs within other glomeruli (Trona et al, 2010;Varela et al, 2011b). Such results are in agreement with data from vertebrates, where both 'common' odours and pheromones can activate the main olfactory bulb and the accessory olfactory bulb (Xu et al, 2005), and thus overlapping processing of both odour types occurs in both compartments of the primary olfactory centre.…”
Section: Mgc Neurons Are Sensitive To a Behaviourally Relevant Plant supporting
confidence: 63%
“…Therefore, any sensory cross-adaptation would need to be broad. Crossadaptation of neurons to odor stimuli has been shown in numerous studies, indicating that processing of different odor stimuli may share common physiological pathways (Daniel et al, 1994;Takeuchi et al, 2003;Gottfried et al, 2006;Anton et al, 2011). Trona et al (2010 recently showed that structurally different sex pheromone and plant odor compounds interact in C. pomonella via an across-fiber coding pattern, with perception of these distinct chemicals relayed through projection neurons from ordinary glomeruli and from the macroglomerular complex.…”
Section: Discussionmentioning
confidence: 99%
“…As for vertebrates, the coding of these two types of odour cues was generally believed to occur in two separate pathways of the insect olfactory system. However, unusual representations of plant odours and pheromones were recently observed in tortricid moths: in Grapholita molesta , pheromone processing seems to occur in OG rather than in the MGC [23] and in Cydia pomonella there is no clear segregation between the pheromone and the general odour sub-systems in the AL, both odour classes being represented in both the MGC and in OG [24].…”
Section: Introductionmentioning
confidence: 98%